FAMILY SOCIAL CAPITAL: ROLE OF FAMILY NETWORKS IN THE CONFLICT RESOLUTION PROCESS OFRECONCILED COUPLES OF LAHORE, PAKISTAN - TAYYABA SOHAIL; AHMED USMAN (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Marital relations are neither created nor operated in isolation. They sprout and flourish within the warmth of family networks. Considering that joint family system is the most prominent family arrangement in Pakistan, the role and position of families cannot be ignored in the marital relation of spouses. They remain active throughout the main stages of the married life including wedding arrangements, marital adjustment phase and completion of marriage. Therefore, the role of families cannot be undermined in conflict management of the spouses. There is a glaring gap in the existing literature regarding the role of family as third party reconciliators in the conflict resolution among spouses. Therefore, the current paper aims to understand the role of family as reconciliator in the conflict resolution process of reconciled couples of Lahore. Using interpretive research paradigm, ten union councilswere selected using purposive sampling having highest number of reconciled couples during the years 2018-2021. The researchers used the records of the union council to contact the reconciliators. 10 reconciled cases were randomly selected from the records and accordingly 20 reconciliators, one from each side, were recruited in the study. The data was collected using in-depth interviews and the technique of thematic analysis was used to draw conclusion. The findings of the study suggestthat the family social capital play a positive role in terms of its function in the conflict resolution of the spouses.